Cytotoxicity of Au, ZnO and SiO2 NPs using in vitro assays with mussel hemocytes and gill cells: Relevance of size, shape and additives. Issue 2 (7th February 2016) - Katsumiti, Alberto; Arostegui, Inmaculada; Oron, Miriam; Gilliland, Douglas; Valsami-Jones, Eugenia; Cajaraville, Miren P.
Abstract: Metal-bearing nanoparticles (NPs) possess unique physico-chemical characteristics that make them useful for an increasing number of industrial products and applications, but could also confer them a higher toxicity due to their higher reactivity compared to bulk forms of the same materials. There is a considerable interest in the use of in vitro techniques in environmentally relevant species, such as marine mussels, to evaluate NPs toxicity. In the present work, mussel hemocytes and gill cells were used to assess the potential toxic effects of Au, ZnO and SiO2 NPs with different sizes and shapes in parallel with their respective ionic and bulk forms and additives used in the NPs preparations. Cytotoxicity (neutral red and MTT assays) was screened at a wide range of concentrations, and LC50 values were calculated. Uptake of fluorescently labeled SIO2 NPs of 27 nm by hemocytes was also investigated. Au, ZnO and SiO2 NPs were less toxic than the corresponding ionic forms but more toxic than the bulk forms. ZnO NPs were the most toxic NPs tested which could be related with their capacity to release free ions. SiO2 NPs were not taken up by hemocytes and were not toxic to either hemocytes or gill cells. Size-dependent toxicity was found for Au NPs. Shape influenced the cytotoxicity of ZnO NPs. Finally, the presence of the additives Na-citrate and Ecodis P90 contributed to the toxicity of Au and ZnO NPs, respectively. As a general conclusion, solubility appears to play a key role in NPs toxicity to mussel cells.